DIFFERENT RESPONSE OF δD VALUES OF N-ALKANES, ISOPRENOIDS, AND KEROGEN DURING THERMAL MATURATION - Pedentchouk N.; Freeman K.H.; Harris N.B. (My University, 2006)
This study investigates the extent of post-depositional alteration of δD values of n-alkyl lipids, isoprenoids, and kerogen isolated from a continuous 450 m core that covers the transition from thermally immature to early mature sediments in the lacustrine Kissenda Formation, Lower Cretaceous, Gabon Basin. Large variations in ?D values (up to 40? for nC17 and up to 30? for nC29 alkanes as well as up to 10? for kerogen) in closely spaced samples are evident throughout the core and remain preserved even at the bottom of the section. ?D values of individual n-alkanes show a slight overall D-enrichment with depth, and a general trend of increasing ?D values with increasing n-alkane chain length characterizes all samples, particularly in those below 600 m depth. Hydrogen isotopic compositions of kerogen samples overlap with those of n-alkanes throughout the section. ?D values of pristane and phytane are more negative than those of nC17 alkane by as much as 120? at shallow depths but increase dramatically and approach ?D values of nC17 alkane in the samples closest to the oil window. Integration of analytical and computational results indicates that: (1) n-alkanes and isoprenoids have the potential to preserve the original biological signal before the onset of oil generation; (2) isomeric and structural rearrangements taking place at the beginning stages of oil generation do not influence significantly the ?D values of n-alkanes and kerogen. However, these processes have a major effect on the isotopic composition of isoprenoids, causing isotopic D-enrichment up to 90?. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ALKANE; DEPOSITION; ENRICHMENT; ISOPRENOID; ISOTOPIC COMPOSITION; KEROGEN; SEDIMENT CHEMISTRY; THERMAL ALTERATION; THERMAL MATURITY; AFRICA; CENTRAL AFRICA; GABON; SUB-SAHARAN AFRICA